The low noise mobilization of community health actors in Senegal : voluntary commitments and professional aspirations - (:unkn) unknown (My University, 2021)
In Europe and the United States, the literature on the practice of volunteering in the health field is more focused on describing the models and social trajectories (economic, religious, or professional) of the actors. In Africa, work of the same type is more concerned with the efficiency of volunteers in the management of community health in rural areas. About our focus, particular emphasis is placed on assessing the roles and responsibilities of the different sub-categories of Community Health Actors (CHA) in the implementation of given programs. This work has paid little attention to the actors themselves, their individual backgrounds, their groupings and their integration into the local fabric. Community empowerment, which has been more than demonstrated, covers a complex reality made up of permanent tensions between different hierarchical systems and the aggregation of partially opposing professional territories. Analyzing the socio-professional mobilization of CHAs allows us to understand their being together, their position in the division of labor and the tense articulation between their different segments.By combining approaches from development anthropology and the sociology of work, volunteering, mobilizations and professional groups, this work offers another look at the organizational repertoires of work construction and professional identities. The investigation analyses how care work is articulated between official, associative, and practical (day-to-day) definitions and examines what types of social link it produces. Based on the cases of Community Health Workers (CHWs) in Senegal, we show that local commitments are a source of social change. Neither a social movement nor a struggle for a profession, the professional mobilization of CHAs is an atopia that rests on the promise that CHAs take care of their development - individual and collective - by pooling their capital of autochthony. This social progress suggests that more importance s
Keywords: African Research